REPRESENTASI CITRA PEREMPUAN DALAM IKLAN VITAGLOW FAIR&LOVELY - Heri Setiawan; Yusuf Sapari; Ahmad Yusron; Dea Angkasa (JIKE: Jurnal Ilmu Komunikasi Efek, 2020)
The development of the times that makes today's society oriented to only one dimension, namely capitalism. Then from this incident was born a new culture of consumerism. In fact, many unknown ideologies have occurred without us realizing it in the environment around us. This study discusses the meaning in the Vitaglow Fair&Lovely mask advertisement which aims to find out what meaning is contained in the advertisement. In this advertisement, John Fiske's Semiotics research method is used, in which there are three levels, namely the level of reality, the level of representation and the level of ideology. The purpose of this study is to find the meaning in the advertisement with three levels, namely the level of reality, representation and ideology. The results of John Fiske's semiotic analysis in VitaGlow Fair & Lovely advertisements, Vitaglow Fair & Lovely advertisements classify 3 images out of 5 existing images, namely Citra Pigura depicting women as formed creatures. The woman in the advertisement is described as having whiter, smoother, and brighter skin after using the VitaGlow sheet mask. The writer's analysis of Vitaglows Fair & Lovely as a whole shows that women must always look good, but remain confident and rise to face problems. The ideological level analysis in the Vitaglows Fair & Lovely video ad depicts femininity which really represents pure women who are cheerful, fun, cares about themselves and cares for other women. The ideology of consumerism represents the message of capitalism where the three advertisements have motivated women not to feel inferior and dare to change their appearance but still lead the dream to change their appearance and make profits. Keywords: level of reality, level of representation, level of ideology, consumerism